Pelatihan Baca Tulis Al-Qur’an (BTQ) Pada Anak-Anak KP.Golat Desa Pangkalan - Mimi Mita Rosadi; Mia Mutmainah; Dede Imtihanudin; Ratna Dewi (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
It is hoped that the results of this paper will become insights as well as initial discourse and action to develop BTQ learning in Islamic educational institutions or in the community. An introduction to reading and writing the Koran to children in this community service activity discussing the introduction of BTQ to children. The purpose of this community service activity is to provide an introduction to the procedures for reading and writing the Qur'an to reveal the effectiveness of implementing the BTQ program at kp.Golat desa. Pangkalan Kab. Pandeglang Banten. The demand for the ability to read and write the Koran has become a widespread phenomenon. Therefore a BTQ program was created for children at kp.Golat desa.pangkalan kab.pandeglang banten. So that with this activity it is hoped that it can improve children's reading and writing of the Koran at kp.Golat desa.pangkalan kab.pandeglang banten, with a variety of BTQ methods provided that can adapt to the needs and characteristics of the children. The diversity of these methods is considered to be able to complement each other's shortcomings with one another. This paper attempts to describe the development of BTQ learning in Sobang Pandeglang with a variety of methods. The results of this paper are attempted to become insights as well as discourse and initial action to develop BTQ learning in Islamic educational institutions or in the community.